151 quick ideas to recognize and reward employees - LLoyd, Ken (The Career Press, 2007)
151 Quick Ideas to Recognize and Reward Employees offers you the full menu of recognition and reward strategies. It comes with detailed descriptions of the most popular ideas in business, plus others that are destined to become classics. Ideas such as: Enriching jobs by giving employees more autonomy and decision-making responsibilities; Purchasing personally signed books suited to the potential you see in each employee; Allowing employees opportunities to attend seminars, classes, or even pursue a degree; Hiring a masseuse to rub out stiff necks and backs; Making your employees more invested by offering profit-sharing; Plus giving out many free or low-cost rewards